Evangelizing the South a social history of church and state in early America - Najar, Monica; Oxford eBooks (New York ; Oxford : Oxford University Press, 2008)
Although many refer to the American South as the 'Bible Belt' the region was not always characterized by a powerful religious culture. In the 17th & early 18th centuries, religion was virtually absent from southern culture. The late 18th & early 19th centuries, however, witnessed an astonishing change.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Church and state -- Southern States; Southern States -- Church history; Southern States -- Social conditions; Electronic books